2023
DOI: 10.1164/rccm.202203-0450oc
|View full text |Cite
|
Sign up to set email alerts
|

SOX17 Deficiency Mediates Pulmonary Hypertension: At the Crossroads of Sex, Metabolism, and Genetics

Abstract: Rationale Genetic studies suggest that SOX17 (SRY-related HMG-box 17) deficiency increases pulmonary arterial hypertension (PAH) risk. Objectives On the basis of pathological roles of estrogen and HIF2α (hypoxia-inducible factor 2α) signaling in pulmonary artery endothelial cells (PAECs), we hypothesized that SOX17 is a target of estrogen signaling that promotes mitochondrial function and attenuates PAH development via HIF2α inhibition. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…SOX17 is a key transcription factor involved in development that affects the cardiovascular system and several endoderm-derived organs [ 44 ]. SOX17 deficiency is linked to pulmonary arterial hypertension (PAH) risk via interactions with Hypoxia Inducible Factor 2 Alpha (HIF-2α) [ 45 ]. TAL1 is also a leukaemia associated transcription factor associated with hematopoiesis [ 45 ], which can act in complex with LMO2, a LIM-domain protein [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOX17 is a key transcription factor involved in development that affects the cardiovascular system and several endoderm-derived organs [ 44 ]. SOX17 deficiency is linked to pulmonary arterial hypertension (PAH) risk via interactions with Hypoxia Inducible Factor 2 Alpha (HIF-2α) [ 45 ]. TAL1 is also a leukaemia associated transcription factor associated with hematopoiesis [ 45 ], which can act in complex with LMO2, a LIM-domain protein [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Walters et al demonstrated that SOX17 enhancer variants lead to downregulation of SOX17 and result in disturbed lung ECs function and PAH through different binding of HOXA5 and ROR-α. Sangam et al 16 reported that SOX17 deficiency inhibits mitochondrial bioenergetics and induces PAH partly via HIF-2α signaling. Zou et al 32 identified SOX17-associated exosomes including microR-224-5p and microR-361-3p improve endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…14 Recent study showed that Sox17 deficiency promoted PH in mice via hepatocyte grow factor (HGF)/c-Met signaling or HIF-2α. 15,16 CRISPR/Cas9-mediated Sox17 enhancer deletion in mice worsened PH. 17 Nevertheless, the exact role of genetic variants or mutation in SOX17 in the contribution of PH remains unclear.…”
mentioning
confidence: 99%
“…Progenesis QI for proteomics software (version 2.4, Nonlinear Dynamics Ltd., Newcastle upon Tyne, UK) was used to perform ion-intensity based label-free quantification as previously described [63][64][65][66]. In brief, in an automated format, .raw files were imported and converted into two-dimensional maps (y-axis = time, x-axis = m/z) followed by the selection of a reference run for alignment purposes.…”
Section: Label-free Quantitative Proteomicsmentioning
confidence: 99%